Women and Entrepreneurship : A Corridor to Financial Inclusion in Bodoland Territorial Area District, Assam - Pradhani, Kripanjali; Choudhury, Soma Roy Dey (AMC Indian Journal of Entrepreneurship, 2018)
According to World Bank, financial inclusion means that individual and businesses have access to useful and affordable financial products and services that meet their needs-including transactions, payments, savings, credit, and insurance-delivered in a responsible and sustainable way. Financial inclusion is the key enabler of economic growth and poverty reduction. Increasing women's financial inclusion is very important as women experience poverty, stemming from unequal divisions of labour and lack of control over economic resources. A wide range of women are dependent on their partner and have no control over household expenditures. Credit constraint is the major barrier for women entrepreneurs of Bodoland Territorial Area District (BTAD), Assam and they have to rely on their family, friends, and moneylenders for starting and running their enterprise. Access to finance to women entrepreneurs will lead to production of quality products and delivery of services which are essential for inclusive economic growth and poverty reduction. So, the present paper will try to find out the relevance of financial inclusion in promoting entrepreneurship among women in BTAD and vice versa. In BTAD area, out of the total women population only 10% are engaged in earning. Though women entrepreneurship in BTAD is still in its nascent stage and entrepreneurial mindset has geared up recently towards opportunity identification, search, and exploitation.